Correlation of Probe-Based Confocal Laser Endomicroscopy (pCLE) and Mucosal Integrity Testing (MIT) with Epithelial Barrier Function and Presence of Gastroesophageal Reflux Disease (GERD) - Mutha, Pritesh R.; Fasullo, Matthew; Chu, Shijian; Schubert, Mitchell L.; Zfass, Alvin; Cooper, Patricia; Gill, Mankanchan; Kang, Le; Vaezi, Michael; Wildhorn, Stu; Slaughter, Chris; Shah, Tilak (Digestive diseases and sciences, 2022)
Introduction Epithelial barrier function (EBF) disruption is a key mechanism underlying gastroesophageal reflux disease (GERD). Our aim was to assess whether two novel technologies, probe-based confocal laser endomicroscopy (pCLE) and mucosal integrity testing (MIT), could assess EBF. Methods We prospectively enrolled patients undergoing upper endoscopy for refractory GERD or non-GERD conditions. Patients underwent esophagogastroduodenoscopy, pCLE, MIT, esophageal biopsy at 2 cm and 6 cm above the esophagogastric junction, and wireless pH testing. To assess EBF in vitro, biopsies were mounted in a mini-Ussing chamber, 1 ml of fluorescein was instilled on the mucosal side, and concentration of fluorescein on the serosal side was measured at 3 h. Results We enrolled 54 subjects (28 GERD, 26 non-GERD based on Lyon consensus criteria). In vivo permeability assessed by pCLE did not differ significantly between GERD vs. non-GERD patients and did not correlate with in vitro permeability. Mean MIT at 2 cm was lower in GERD compared to non-GERD (1914 vs. 3727 ohms). MIT correlated inversely with in vitro permeability at 2 cm and at 6 cm. Using a predictive model that used slope and intercept of MIT at 2 cm and 6 cm, sensitivity and specificity of MIT at identifying GERD was 76% and 72%, respectively. Conclusion pCLE did not differentiate GERD vs non-GERD and did not correlate with EBF measured in vitro. MIT, on the other hand, may be more promising as it differentiated GERD vs non-GERD and correlated with EBF measured in vitro.